Contested Waters - Widiyanto, Andika (PCD Journal, 2024)
This study examines the mechanisms of community access to water from the Cipasauran River, Serang Regency, Banten, which has been disrupted by damming activities carried out by PT Krakatau Tirta Industri (PT KTI). Employing a qualitative approach with a case study design, this research maps the distribution of water resource benefits, identifies the mechanisms used by various actors to obtain, control, and sustain access, and analyses the power dynamics that shape these mechanisms. Findings reveal that companies predominantly benefit from the river’s water resources through multiple access mechanisms, thereby restricting local communities’ access. Additionally, ecological changes caused by the dam have further exacerbated these restrictions. The study concludes that the allocation of Cipasauran River’s water resources is largely skewed in favour of the company’s interests, facilitated by legal and relational-structural mechanisms. Furthermore, asymmetric power relations among actors have reinforced disparities in water access.